Analisis Pengaruh ROE dan DAR Terhadap Harga Saham - Nova Diella Ebygael Pakpahan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine the effect of ROE and DAR on stock prices either simultaneously or jointly and partially or individually at PT Pembangunan Perumahan Properti Tbk for the 2016-2020 period. This study uses a descriptive method with a quantitative approach. The object of this research is PT PP Properti Tbk with secondary data originating from the quarterly financial statements for the 2016-2020 period. Analysis of the data used is multiple linear regression analysis. The results showed that the results of the t-test showed that DAR and ROE partially/individually did not have a significant effect on stock prices. While the simultaneous results of DAR and ROE have a significant effect on stock prices based on the F test.